2009
DOI: 10.1142/s0217979209049577
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION OF AlN THIN FILMS FABRICATED BY REACTIVE DC SPUTTERING: EXPERIMENTAL MEASUREMENTS AND HÜCKEL CALCULATIONS

Abstract: A set of AlN thin films was prepared by reactive magnetron sputtering at room temperature. The effect of oxygen impurities on the structural and optical properties of AlN films is discussed. The structural and optical properties were characterized using X-ray diffraction (XRD) and spectroscopic ellipsometry, respectively. Depending on the deposition conditions, films can grow hexagonal (würzite, P 63 m 3) or cubic (zinc-blende, Fm3m) in microstructure. From the optical measurements, the ellipsometric parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…From this table, it can be observed that there is a decrease in band gap from 5.48 to 5.00 eV and a substantial decrease in ∞ (optical contribution to the dielectric function at a higher photon energy) when the nitrogen/argon flow ratio was increased from 30 to 80%. Similar results on band gap variation of AlN thin films have been reported by García-Méndez et al [19]. However, our results are contrary to those of Cho [13] and Wang et al [15], who have used RF magnetron sputtering technique.…”
Section: Spectroscopic Ellipsometry Resultssupporting
confidence: 78%
“…From this table, it can be observed that there is a decrease in band gap from 5.48 to 5.00 eV and a substantial decrease in ∞ (optical contribution to the dielectric function at a higher photon energy) when the nitrogen/argon flow ratio was increased from 30 to 80%. Similar results on band gap variation of AlN thin films have been reported by García-Méndez et al [19]. However, our results are contrary to those of Cho [13] and Wang et al [15], who have used RF magnetron sputtering technique.…”
Section: Spectroscopic Ellipsometry Resultssupporting
confidence: 78%
“…The XRD peaks at 2θ = 33.1, 35.9, and 37.8°can be assigned to the (100), (002), and (101) reflections respectively, of a wurzite hexagonal-phase with lattice parameters of a = 3.1114 Å and c = 4.9792 Å. 18 The peak of highest intensity at 2θ = 33.1°indicated that the sample is mainly formed by crystallites oriented at the a-axis direction. Curren-tÀvoltage (IÀV) curve of the ITO contacts (separated by a distance d = 10 μm) deposited on a 200 nm thick AlN layer was also measured, see Figure 2d.…”
Section: ' Results and Discussionmentioning
confidence: 92%
“…Figure c gives the X-ray diffraction (XRD) pattern of the as-grown AlN thin film deposited on the p -GaN/sapphire. The XRD peaks at 2θ = 33.1, 35.9, and 37.8° can be assigned to the (100), (002), and (101) reflections respectively, of a wurzite hexagonal-phase with lattice parameters of a = 3.1114 Å and c = 4.9792 Å . The peak of highest intensity at 2θ = 33.1° indicated that the sample is mainly formed by crystallites oriented at the a -axis direction.…”
Section: Resultsmentioning
confidence: 96%
“…However, it must be stressed out that our proposed method is simple, computationally efficient and the electronic structures obtained can be optimized to closely match the experimental and/or ab-initio results. More specific details about DOS graphs and PDOS calculations can be found in reference (García-Méndez et al, 2009), of our authorship.…”
Section: Theoretical Calculationsmentioning
confidence: 99%